Do children choose to play active video games when given the choice between seated and ambulatory video game play? A study of children`s play choice. - Mellecker, R. R.; Lanningham-Foster, L.; Levine, J. A.; McManus, A. M. (International Journal of Computer Science in Sport, 2012)
Background: The development of active gaming offers a choice for children to be physically active whilst participating in an activity that is enjoyable and highly valued. Children expend energy when they play activity enhanced video games, yet little is known about their choice when given active alternatives over seated play. Methods: This study examined (i) choice of play between a seated video game option or the same game played ambulatory; (ii) consistency in play choice with sustained play. Play behavior was recorded from postural monitoring and observation. Repeated measures analyses of variance were used to determine differences in total time, percentage of time and consistency of choice in each condition. Results: Play choice was consistent over the four sessions with 76%, 23% of the available time spent seated and ambulatory, respectively. Follow up analysis indicated that the time spent playing in each condition was constant across all four video game sessions. Conclusions: These preliminary findings demonstrate that when given freechoice children will predominantly play video games seated. The advancement of active video gaming as an active alternative is dependent on future investigations into whether these innovative technologies offer enough entertainment value to sustain long-term adherence.